The Search for Ixodes dammini and Borrelia burgdorferi in Nova Scotia - Colin R Bell; Harold B Specht; B Ann Coombs (Canadian Journal of Infectious Diseases)
Twenty-four Ixodes dammini ticks (23 adults and one nymph) have been recovered in Nova Scotia since 1984. There has not been a systematic search for larvae and none has been identified. The recovery of the nymph from a road-killed yellow throat bird, Geothypis trichas, in late May 1990 supports the contention that migrating birds are bringing deer ticks into the province every spring. In March and April 1991, four adult deer ticks were identified, suggesting that these ticks had overwintered. These deer tick specimens indicate that it is possible that I dammini is becoming established in Nova Scotia, if it is not already established. There has been no evidence for the existence of Borrelia burgdorferi in the province. The spirochete was not cultured from 650 Dermacentor variabilis ticks, nor were antibodies detected in a small sample of feral rodents using an indirect fluorescent antibody test. A survey of 137 dog sera samples, analyzed by enzyme-linked immunosorbent assay, also proved negative. There has been no confirmed indigenous case of Lyme disease in Nova Scotia to date.